SMK BAU HOSTEL MANAGEMENT SYSTEM - Kuan, Sze Li (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Hostel Management system is software developed for managing the school hostel, which includes storing the information of the students, generate report for room availability and manage room allocation. This project also deals with the problems on managing a hostel and prevents problems which occur during the manual work that had been carried out for managing the hostel. Identification of the drawbacks of the manual work leads to the designing of this computerised system. Through computerizing the existing system with the help of C#. NET which are an object-oriented programing language, it is hoped that it will be compatible with the existing system and will be more efficient and user friendly.